Ground effects on the hypervelocity jet flow and the stability of projectile. Issue 1 (1st January 2018) - Li, Zijie; Wang, Hao; Chen, Jianwei
ABSTRACT: The significant influence of the ground on the hypervelocity jet flow as well as the stability of the projectile cannot be discarded due to the intensity and the wide influence range. The present study examines two three-dimensional simulation models, one with the ground effects included and the other without, based on FLUENT software, using the finite volume method (FVM). The simulation models couple the FVM model with a standard k-ε turbulence model and unstructured dynamic grid based on the Local Remeshing method. An intermediate ballistic model and the six-degrees-of-freedom model are also utilized. For the 300-caliber 1730 m/s countermass propelling gun, two different flow phenomena, with and without the ground effects, were examined. The simulation results indicate that the effect of the ground surface on the jet flow and the projectile emerged gradually at 1.5 ms. The hypervelocity muzzle shock wave was reflected off the ground, creating a new shock-wave phenomenon in the opposite direction. The wave system interacted with the muzzle shock wave so that the pressure in the lower half of the domain was significantly higher than that in the upper half. This phenomenon produced a complete shock-wave surface. Shock waves at the ground produced a vortex, which gradually expanded and developed. The wavefront, which was formed by the ground reflection, led to a new wavefront, producing vortices at the wavefront and propagated towards the front and rear of the main shock wave. The hypervelocity jet flow twisted and generated a more complex wave system. The distorted gas jet caused the projectile to be disturbed, and the lift and torque were influenced so that the parameters such as the angular velocity of the rotation were changed.